Study of Various Soil Stabilization Techniques That Suitable for Parit Nipah Peat Soil - Mohd, Ros Halimatun Airien; Mohd Salleh, Anuar (Recent Trends in Civil Engineering and Built Environment, 2022)
Peat soil is defined as soil with a high percentage of decomposed organic materials. The great majority of peatland lands have been redeveloped for agricultural purposes. Peat soil is categorised as problematic soils and dangerous for engineering structures because of geotechnical properties including high compressibility and weak shear strength. This paper presents various method of soil stabilizer by various type of admixture. The method review was electrokinetic stabilization, cement lime stabilization and envirotac Stabilization. The research is carried out by analysing prior case studies conducted by other experts. The case study was taken at Prt. Nipah Johor Malaysia. In this study, the method of the soil stabilizer that taken from other state in Malaysia that have the same physical and mechanical properties of peat soil of study area were discuss in order to find the suitable method of peat soil stabilizer for Prt. Nipah Johor. Some engineering variables were compared with the physical and chemical properties of the peat soil at Prt. Nipah Johor including unconfined compressive strength (UCS), the liquid limit test, and moisture test result from the previous study of the untreated and treated peat soil. From the study, the suitable peat soil stabilization method has been identified which cement lime stabilization method. This is due to the condition that more suitable compared to the other two methods.